2018
DOI: 10.1007/s40519-018-0495-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Italian Yale Food Addiction Scale in postgraduate university students

Abstract: Level V, descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…The validity of the Russian translation of YFAS‐C confirmed by the existence of a significant association (logistic regression, N = 100; odds ratio [OR] 95% confidence interval (CI) 2.34 [1.65, 3.32], P < 0.0001) between FA and Emotional Eating subscale of Dutch Eating Behavior Questionnaire (Van Strien, Frijters, Bergers, & Defares, ). Similar association was described earlier (Gearhardt et al, ; Manzoni et al, ).…”
Section: Methodssupporting
confidence: 91%
“…The validity of the Russian translation of YFAS‐C confirmed by the existence of a significant association (logistic regression, N = 100; odds ratio [OR] 95% confidence interval (CI) 2.34 [1.65, 3.32], P < 0.0001) between FA and Emotional Eating subscale of Dutch Eating Behavior Questionnaire (Van Strien, Frijters, Bergers, & Defares, ). Similar association was described earlier (Gearhardt et al, ; Manzoni et al, ).…”
Section: Methodssupporting
confidence: 91%
“…Specifically, scores on the dYFAS-C 2.0 were positively associated with emotionally and externally triggered consumption, constructs also implicated in SUDs (Joyner et al, 2015;Loxton & Tipman, 2017;Manzoni et al, 2018). Prior food addiction research in adults and children with other versions of the YFAS have found similar associations with emotional and externally triggered eating (Brunault et al, 2017;Clark & Saules, 2013;Gearhardt et al, 2009Gearhardt et al, , 2016Loxton & Tipman, 2017;Manzoni et al, 2018). These findings suggest that interventions to increase emotion regulation (e.g., mindfulness) and the ability to cope with environmental triggers (e.g., craving management) may be beneficial for adolescents endorsing indicators of food addiction, although future research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The YFAS applies the Diagnostic and Statistical Manual fourth edition (DSM‐IV) criteria for substance dependence (e.g., loss of control, tolerance, and withdrawal) to the problematic consumption of highly palatable foods. In adult samples, the YFAS has been associated with factors implicated in addiction, such as increased consumption in response to emotions and environmental cues (Clark & Saules, ; Gearhardt et al, ; Joyner, Schulte, Wilt, & Gearhardt, ; Loxton & Tipman, ; Manzoni et al, ). The YFAS is also associated with negative consequences related to overeating, such as obesity (Gearhardt et al, ; Innamorati et al, ; Pursey, Stanwell, Gearhardt, 0Collins, & Burrows, ; Torres et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The structured questionnaire included 25 questions, divided into three different sections: (1) personal and general data (including 6 questions: age, gender, information on region and province of residence, level of education, and cohabitation situation at home); (2) anthropometrics information (including 2 questions reported as weight and height); (3) lifestyle, eating habits changes, psychological and emotional aspects caused by the social isolation during the pandemic period (including 17 questions modified from validated tools [ 19 , 20 , 21 , 22 , 23 ]), to investigate and assess the emotional aspects such as anxiety, depressed mood, hypochondria, level of concern, emotional eating, insomnia, dietary changes, as well as the perception of diet control and appetite. No names or other personal information was requested.…”
Section: Methodsmentioning
confidence: 99%